The major leucyl aminopeptidase of Trypanosoma cruzi (LAPTc) assembles into a homohexamer and belongs to the M17 family of metallopeptidases - Cadavid-Restrepo, Gloria Ester (2011)
Background Pathogens depend on peptidase activities to accomplish many physiological processes, including interaction with their hosts, highlighting parasitic peptidases as potential drug targets. In this study, a major leucyl aminopeptidolytic activity was identified in Trypanosoma cruzi, the aetiological agent of Chagas disease. Results The enzyme was isolated from epimastigote forms of the parasite by a two-step chromatographic procedure and associated with a single 330-kDa homohexameric protein as determined by sedimentation velocity and light scattering experiments. Peptide mass fingerprinting identified the enzyme as the predicted T. cruzi aminopeptidase EAN97960. Molecular and enzymatic analysis indicated that this leucyl aminopeptidase of T. cruzi (LAPTc) belongs to the peptidase family M17 or leucyl aminopeptidase family. LAPTc has a strong dependence on neutral pH, is mesophilic and retains its oligomeric form up to 80°C. Conversely, its recombinant form is thermophilic and requires alkaline pH. Conclusions LAPTc is a 330-kDa homohexameric metalloaminopeptidase expressed by all T. cruzi forms and mediates the major parasite leucyl aminopeptidolytic activity. Since biosynthetic pathways for essential amino acids, including leucine, are lacking in T. cruzi, LAPTc could have a function in nutritional supply.